Health information systems: proposal of a provenance data management method in the instantiation of the W3C PROV-DM model - Sembay, Márcio José; Jeronimo de Macedo, Douglas Dyllon (Advanced Notes in Information Science, 2022)
Health Information Systems (HIS) are being implemented in all aspects of health, from administration to clinical decision support systems. The generation and storage of large volumes of data in their decentralized repositories make these processes challenging when it comes to managing this data. The data provenance approaches in this regard help to answer questions such as: why? How? Where? When? by whom? And for what? The data were produced in the HIS, contributing to several benefits, especially in terms of traceability of the data of origin so that they can be managed within these systems. In this context, the present work is bibliographical research of qualitative nature based on the Provenance Data Model (PROV-DM) recommended by the World Wide Web Consortium (W3C), where we propose a method for management of provenance data in HIS. Considering the theme of this study, the research question presented here is: how to develop a method for the management of provenance data in HIS in the instantiation of the W3C PROV-DM model? An expected result is the development of a prototype to validate the method proposed here in a real health scenario, showing, in fact, the benefit of using the method.